2017
DOI: 10.1371/journal.pone.0178996
|View full text |Cite
|
Sign up to set email alerts
|

Development and external validation of a clinical prognostic score for death in visceral leishmaniasis patients in a high HIV co-infection burden area in Ethiopia

Abstract: BackgroundIn Ethiopia, case fatality rates among subgroups of visceral leishmaniasis (VL) patients are high. A clinical prognostic score for death in VL patients could contribute to optimal management and reduction of these case fatality rates. We aimed to identify predictors of death from VL, and to develop and externally validate a clinical prognostic score for death in VL patients, in a high HIV co-infection burden area in Ethiopia.Methodology/Principal findingsWe conducted a retrospective cohort study in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…The predictors of death identified—age >40 years and hemoglobin level ≤6.5 g/dL—are similar to those reported from other studies [ 35 , 48 , 49 ]. Patients aged >40 years, may have underlying co-morbidities (e.g.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The predictors of death identified—age >40 years and hemoglobin level ≤6.5 g/dL—are similar to those reported from other studies [ 35 , 48 , 49 ]. Patients aged >40 years, may have underlying co-morbidities (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, we had a higher admission rate of late stage VL patients that were referred from other hospitals as compared to the previous AmBisome monotherapy study. We have recently shown that besides HIV serostatus, other important predictors of death were: age >40 years, hemoglobin ≤6.5 g/dL, bleeding, jaundice, edema, ascites and tuberculosis [ 35 ]. We also found that in the presence of major predictors of death, the predictive effect of treatment on outcome may be minimal [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations